Basic mechanical analysis of soccer ball impact - Iga, T.; Nunome, H.; Inoue, K.; Ikegami, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The present study aimed to provide a reference of the nature and the magnitude of the ball reaction force during ball impact. A soccer ball directly fired to the force platform and the sagittal motion was captured at 5000Hz. The peak forces and impulses during ball contact were computed from the displacement of the ball geometric centre (CB force / impulse) and the centre of the gravity (CGB force / impulse), and those values were compared with the force directly measured from the force platform (D force / impulse). Overall, the CGB forces were comparable to the D force while the CB forces were substantially overestimated. Those impulses were well matched with the theoretical value computed from the change of ball momentum before and after the contact. Those findings of the present study confirmed the reliability of the CGB model.